Defining the Onset of Fajr: An Evaluation of Comparative Evidence of Solar Depression Standards in Indonesia - Musliatin; Siti Tatmainul Qulub; Ahmad Adib Rofiuddin; Firqi Hidayat (Universitas Islam Negeri Mataram, 2026)
In 2010, an issue circulated in Indonesia claiming that the Fajr prayer time was set too early, which was published in Qiblati Magazine at that time. This issue eventually received responses from experts in Islamic Astronomy (Ilmu Falak), who then conducted a re-examination of the determination of the Fajr prayer time. After years of conducting a re-examination, the researchers eventually reached a conclusion and decided that the solar altitude criterion for the beginning of the Fajr prayer time used by the Ministry of Religious Affairs of the Republic of Indonesia and Nahdlatul Ulama was already appropriate, while it differed from the criterion used by Muhammadiyah. The study entitled “Defining the Onset of Fajr: An Evaluation of Comparative Evidence of Solar Depression Standards in Indonesia” aims to compare the foundations used by these three institutions in determining the Sun’s altitude at dawn. This research employs a descriptive qualitative method with a comparative and library-based approach. The findings show that the three institutions determine the beginning of the Fajr (Subuh) prayer time based on the appearance of true dawn (fajr sadiq) on the eastern horizon, which is used as the sign for the start of the Subuh prayer time, as stated in Q.S. Al-Baqarah verse 187. There are differences of opinion regarding the most preferable time to perform the subuh prayer. The Ministry of Religious Affairs holds that there are two possible times, namely ghalas and isfar. Meanwhile, Nahdlatul Ulama and Muhammadiyah consider ghalas to be the more preferable time. However, the similarity among these three institutions lies in the shar’i foundation they use, the main instruments employed, and the resulting decisions. Furthermore, the practical contribution of the study is the development and establishment of an SOP (Standard Operating Procedure) for research related to the Fajr or dawn prayer time. This SOP aims to ensure consistent results and to optimize its implementation so that it can be applied effectively in various regions across Indonesia.